Assessment On Effects Of Procurement Process Through The Use Of Gpsa Framework Agreement On Public Entities In Tanzania: A Case Study Of National Auditing Office (NAO) - William L. Mboma (Cita Konsultindo Research Center, 2022)
The aim of this Study is to Assessment on the Effects of Procurement Process through the use of GPSA Framework Agreement on Public Entities, the National Auditing Office (NAO) was a case of study. The study guided with three objectives which are to examine the GPSA framework Agreement process and procedures used by PEs to purchase common items, To examine the cost minimization and shorten delivery time of common goods to PEs as a purpose of the framework Agreement and to examine if the framework Agreement for common use items minimize cost and time used by suppliers to participate in tender. A research was a descriptive study, and it use both primary and secondary data. Observation, interview and questionnaire were the methods/techniques used to collect primary data. Reviewing government publication, earlier research and mass media was a source of obtain secondary data. A sample size was 45 respondents, 39 was selected purposefully from NAO staff and 6 were different suppliers companies. Data was analysed qualitatively as well as quantitatively. A qualitative presentation will involve the description and explanation of data which obtained whereas quantitative presentation involved presentation of data in the form of table, figure and numerical through SPSS. The findings of this study is “ the use of Framework Agreement System for Common use Items and Services through tendering procurement process and other procurement method minimizes procurement costs as well as reduction of delivery time of the goods and services to the procuring entities. However, there is delay in tendering procurement process and late award of contracts”. Development of E-procurement to enhance to reduce delay in contract award, awareness creation to procurement stakeholders was recommended by a researcher as a solution at NAO on solving challenges rises as the results on using framework agreement